Aqueous acid-based synthesis of lead-free tin halide perovskites with near-unity photoluminescence quantum efficiency. Issue 17 (26th March 2019) - Wang, Aifei; Guo, Yanyan; Zhou, Zhaobo; Niu, Xianghong; Wang, Yonggang; Muhammad, Faheem; Li, Hongbo; Zhang, Tao; Wang, Jinlan; Nie, Shuming; Deng, Zhengtao
Abstract : Aqueous acid-based synthesis of lead-free tin halide perovskites with near-unity photoluminescence quantum efficiency and high chemical yield is described. Abstract : Recently, lead halide perovskites with outstanding emission performance have become new candidate materials for light-emitting devices and displays; however, the toxicity of lead and instability of halide perovskites remain significant challenges. Herein, we report the aqueous acid-based synthesis of highly emissive two-dimensional (2D) tin halide perovskites, (octylammonium)2 SnX4 (X = Br, I, or mixtures thereof), which displayed a high absolute photoluminescence (PL) quantum yield of near-unity in the solid-state, PL emission centered at 600 nm with a broad bandwidth (136 nm), a large Stokes shift (250 nm), long-lived luminescence ( τ = 3.3 μs), and zero overlap between their absorption and emission spectra. Significantly, the stability study of 2D tin halide perovskites monitored by the PL quantum yield showed no changes after 240 days of storage at room temperature under ambient air and humidity conditions. The PL emission of the 2D tin halide perovskites was tuned from yellow to deep red by controlling halide composition. Furthermore, new yellow phosphors with superior optical properties are used to fabricate UV pumped white light emitting diodes (WLEDs). We expect these results to facilitate the development of new environmentally friendly and high-performance phosphors for future lighting and display technologies.